USE OF BOTULINUM TOXIN TYPE A IN THE TREATMENT OF SPASTICITY IN CHILDREN WITH CEREBRAL PALSY - Ljiljana Lazić (Acta Medica Medianae, 2011)
Cerebral palsy has an incidence of about 1-2 per 1000 live births, and in spite of the progress of neonatal medicine, it seems that the incidence will not subside in the near future. The most important characteristic of cerebral palsy is movement abnormality: spasticity, chorea, athetosis, ataxia, dystonia, as well as their different combinations. About 70% of children who suffer from cerebral palsy also suffer from some form of spasticity. Spasticity is a type of muscle hypertonicity characterized by rapid increase in resistance to passive stretching of muscles. The interest for botulinum toxin application in the treatment of spasticity has dramatically increased in the last 10 years. Botulinum toxin is the most powerful neurotoxin that is found in nature. It is produced by anaerobic bacteria – clostridium botulinum. It is produced in eight serotypes of which type A is the most commonly used. Botulinum toxin blocks neuromuscular transmission and causes irreversible weakness of the treated muscle. It has been used since 1993 in the treatment of cerebral palsy in children. The toxin effect is permanent and it results in irreversible denervation. Functional recovery is possible after 2-4 months, due to sprouting of nerve endings and the formation of new synaptic contacts. Treatment with botulinum toxin is safe. Adverse effects are rare, temporary and completely reversible. Application of botulinum toxin prevents or reduces contractures and deformities, and thus delays or avoids surgical treatment. Yet, physical therapy, which prolongs and improves the effects of botulinum toxin, remains an essential and most important form of therapy in the treatment of children with cerebral palsy.